Evolutionary optimization of material removal processes - Singh, Ravi Pratap (Boca Raton : CRC Press, 2023)
"This text covers the latest machining processes using evolutionary optimization and comparative analysis with conventional optimization techniques. It will an ideal reference text for graduate students and academic researchers working in diverse engineering fields including mechanical, aerospace, industrial, manufacturing, and materials science"--
Experimental investigation of surface roughness for turning of UD-GFRP composite using PSO, GSA and PSOGSA technique / Meenu and Surinder Kumar -- Multi-response optimization during high-speed drilling of composite laminate using grey entropy fuzzy (GEF) and entropy based weight integrated multi-variage loss function / Jalumedi Babu, Khaleel Ahmed, Lijo Paul, Abyson Scaria, and J. Paulo Davim.
OCLC-licensed vendor bibliographic record.
Keywords: Machining -- Data processing; Cutting -- Data processing; Evolutionary computation; Mathematical optimization; TECHNOLOGY / Manufacturing; TECHNOLOGY / Material Science